Disease Incidence and Severity of Paddy Bunt in Punjab during 1996-2004 - R.C. SHARMA,; GURMIT SINGH,; NAVRAJ K. SARAO,; MONIKA A. JOSHI, (Seed Research, 2026)
Under the disease monitoring programme in Punjab, 218, 1049, 1759, 1155, 889, 1286, 1252, 1052 and 936 samples of paddy (Oryza sativa L.) were collected, respectively, for the years 1996-2004 for analysis of paddy bunt (kernel smut) caused by Tilletia barclayana (Neovossia horrida). The disease incidence (per cent infection) and disease severity (coefficient of infection) were worked out for the last nine years. The average disease severity was lowest (0.33) in 2004 and highest (0.47) in 2001 and 2003 as compared to the previous years when the severity remained almost constant at (~0.41). Three clear-cut zones of the disease have emerged in Punjab, The South-western districts of the state like Bhatinda, Faridkot, Ferozepur, Moga and Sangrur have been identified as areas of high disease severity/infection per cent (0.63/9 1.0), respectively, while Central and North-western districts like Kapurthala, Patiala, Ludhiana, Amritsar and Jallandhar had moderate disease severity/infection per cent (0.36/87.0), North-eastern parts of the state viz. Hoshiarpur, Fatehgarh Sahib, Gurdaspur, Nawanshehar and Ropar represented the areas of low (0.26/78.8) disease severity/infection per cent. Among the prevalent varieties in Punjab, PR 108 was observed to be most susceptible to bunt as it had maximum severity (2.32) as well as per cent infection (93.59) followed by PR 113 (0.57/89.92) and PR 111 (0.50/87.20).